Sosialisasi Atas Perubahan Skema Perhitungan PPh Pasal 21 Kepada Siswa SMK Negeri 3 Depok - Masripah, Masripah; Widyastuti, Shinta; Arieftiara, Dianwicaksih; Nabby, Eyglus (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Government Regulation Number 58 of 2023 brings significant changes to the calculation of Income Tax (PPh) Article 21, which will take effect in January 2024. These changes not only affect company employees but are also important for Vocational High School (SMK) students who will work as tax staff. A community service activity in the form of a socialization about the changes in the PPh Article 21 calculation scheme was conducted for 75 students of the 11th grade in Accounting and Financial Institutions at SMK Negeri 3 Depok on July 22, 2024. This socialization aims to provide a deep understanding and enhance students' readiness for the workforce. The methods used include practical socialization accompanied by pre-tests and post-tests to measure students' understanding. The results show an increase in students' understanding from 69.5% before the socialization to 94.2% after the socialization. This activity successfully improved students' knowledge of taxation and its relevance to national economic development.